Horticulture Exports, Agro-industrialization and Farm-nonfarm Linkages with the Smallholder Farm Sector: Evidence from Senegal - Miet Maertens (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
In this paper we address the question of firm-nonfirm linkages at the household level for a case-study in Senegal. We examine whether increasing off-firm employment opportunities for rural households ?resulting from increased horticulture exports and associated agro-industrialization ?has benefitted the smallholder firm sector through investment linkages. We use data from a household survey in the main horticulture export region in Senegal. We find that access to unskilled employment in the export agro-industry has contributed to alleviation firmers?liquidity constraints, resulting in increased smallholder agricultural production.
Keywords: J23; O12; Q12; Q17; 330; farm-nonfarm linkages; agri-food exports; smallholder farming; rural development; Gartenbauprodukt; Außenhandel; Agroindustrie; Ländliches Einkommen; Landwirtschaftlicher Familienbetrieb; Agrarproduktion; Senegal